Investigation of Drag Force and Downforce on Two Racing Motorcycles in Slipstream Conditions - Hanifudin, Muhamad; Jatisukamto, Gaguk; Darsin, Mahros; Kustanto, Muh. Nurkoyim; Saleh, Azmi; Prasetyono, Suprihadi; Sarwono, Catur Suko (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
The performance of modern racing motorcycles is greatly influenced by their aerodynamics. Slipstreaming occurs during a race when a rider closely follows another, especially on a straight track. The effect can reduce aerodynamic drag and increase the overall speed of the rider behind. This study investigates the aerodynamic effects of slipstreaming on a racing motorcycle using computational fluid dynamics. This study also considers its effect on both drag force and downforce, which affects motorcycle stability. A 3D CAD model of a racing motorcycle and a rider in a crouching position was used as the object of research. CFD simulations were carried out using the RANS Steady State solver with the k-ω-SST turbulence model. The simulations evaluated the effect of varying distances between motorcycles on slipstream performance, as well as varying motorcycle speeds. The results show the effect on drag force and downforce for the trailing motorcycle. This is due to the shielding effect of the motorcycle in front, which creates a low-pressure zone behind it. Additionally, the turbulence behind the racing motorcycle also affects its downforce. Optimizing the distance between motorcycles in the slipstream allows riders to improve overtaking performance. It also reduces adverse effects on motorcycle stability caused by the slipstream's influence on downforce. Furthermore, it can be used to develop aerodynamic modifications to racing motorcycles that can utilize the slipstream more effectively.